Preparation and evaluation of high-performance modified alkyd resins based on 1,3,5-tris-(2-hydroxyethyl)cyanuric acid and study of their anticorrosive properties for surface coating applications - Al-Zahrani Fatimah Ali M.; Lin Long; Abd El-Wahab Hamada (e-Polymers, 2022)
By partially substituting 1,3,5-tris-(2-hydroxyethyl) cyanuric acid for glycerol as the polyol, new modified alkyd resins having a wide range of oil length and hydroxyl content were produced. FT-IR, 1H NMR, acid and iodine values, and other characterization techniques were used to confirm the chemical compositions of the modified alkyd resins. The drying qualities of the alkyd resins synthesized were significantly enhanced by adding a greater quantity of freshly prepared polyol and excess –OH, along with improvements in flexibility, gloss measurement, gloss measurement, and scratch hardness, in comparison to unaltered alkyd resin (blank). The corrosion resistance of dried coated steel panels was examined using a salt spray test. By using a specifically designed modified alkyd resin as a binder, the corrosion resistance of painted steel panels was improved. The addition of the new polyol, which contains nitrogen components, as well as the alkyd resins that provide strong adherence to the steel surface, may be responsible for such an improvement.